Numerical simulation of random fields using correlated random vector and the Karhunen-Loève expansion - Poński, Mariusz; Pokorska, Iwona (Computer Assisted Methods in Engineering and Science, 2018)
This paper presents an approach of one- and two-dimensional random field simulation methods using a correlated random vector and the Karhunen–Loève expansion. Comparison of the authors’ analytical solution of the Fredholm integral equation of the second kind with the numerical solution using the finite element method and the inverse vector iteration technique is presented. Numerical approach and sample realizations of one- and two-dimensional random fields are presented using described techniques as well as generated probability distribution functions for chosen point of the analysed domain.